Intervensi Holistik dalam Perawatan Bayi Kecil: Sinergi Buku KIA dan Health Coaching untuk Meningkatkan Kualitas Asuhan - Suni Hariati; Erfina Erfina; Dian Sidik Arsyad; Andriani Andriani; Nurmaulid Nurmaulid; Tuti Seniwati; Eva Febrianty; Andi Tizaly Nurul Istighfari; Nadya Salsabila Ramadhani; Andi Miftahul Jannah; Kamlia Ramadhani; Agnes Claudia Pas (Universitas Baiturrahim, 2026)
Kaluku Bodoa Community Health Center in Tallo District is among the top three areas with the highest incidence of low birth weight (LBW) cases in Makassar, recording 48 cases in 2022. A 2024 study revealed that many LBW infants had not received neonatal home visits and did not possess the Small Baby MCH Book, further exacerbated by the lack of socialization and training among health workers. Through the integration of the Healthy Indonesia Program with Family Approach (PIS-PK), empowering community health cadres in small baby care is essential to prevent stunting. This community service program aimed to enhance cadre capacity through managerial training, utilization of the Small Baby MCH Book, and the establishment of an online support forum for mothers with small infants. The activities were implemented through technical training on the integration of the Small Baby MCH Book and health education using a health coaching approach for health workers and cadres, followed by mentoring sessions at pilot Posyandu through book distribution and educational sessions using visual and guideline-based media The results of the activity demonstrated an increase in the average knowledge and skills of community health cadres and maternal and child health (MCH) healthcare providers in delivering services for mothers and infants with a history of low birth weight, with scores improving from 46.7 on the pre-test to 60.4 on the post-test., and successfully initiated the implementation of a dedicated Posyandu for LBW infants. Targeted care for small babies is a crucial effort to prevent future growth and developmental disorders, emphasizing the need for special attention and differentiated care from health professionals and cadres.